Prevalence of Methicillin-Resistant Staphylococcus aureus (MRSA) And Extended-Spectrum B-Lactamases (ESBLs) Producing Enterobacteriaceae Among Nosocomial Bacteria in Kaduna, Nigeria (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Despite continuous control efforts, antimicrobial resistance remains a global public health problem that undermines the treatment of infectious diseases. Methicillin-resistant Staphylococcus aureus (MRSA) and Extended-spectrum -lactamases (ESBLs) producing bacteria represent two important groups of multi-drug resistant pathogens that are associated with a high rate of treatment failure, prolonged morbidity, and increased cost of treatment. Therefore, keeping such superbugs under surveillance, particularly in healthcare facilities, is required for informed action, designing of control interventions for further antimicrobial emergence, and determining strategies for infection control. Thus, this study was designed to determine the prevalence of MRSA and ESBLs production Enterobacteriaceae isolated from four hospitals. Using CLSI guidelines, a total of 96 S. aureus were screened for methicillin resistance, and 137 isolates of Enterobacteriaceae for ESBLs production. The study observed a prevalence rate of 35.42 % for MRSA and 26.3 % for ESBLs production among Enterobacteriaceae. Furthermore, species-wise analysis of the data indicated the individual prevalence rate of ESBLs production among E. coli, K. pneumoniae, and P. aeruginosa to be 25.6 %, 28.8 % and 23.0, respectively. This indicates the occurrence of antimicrobial resistance strains among bacteria isolated from hospital settings. The results obtained here could be important in informing public health policies/strategies for the control of antimicrobial resistance and infection.
Keywords: Methicillin-resistant Staphylococcus aureus (MRSA); Extended-spectrum B-lactamases (ESBLs); Enterobacteriaceae; Nosocomial bacteria; Kaduna